[RETRACTED ARTICLE] Comparison of Arndt-endobronchial blocker plus laryngeal mask airway with left-sided double-lumen endobronchial tube in one-lung ventilation in thoracic surgery in the morbidly obese - Zhang,Z.J. (2018)
This study aimed to evaluate the feasibility and performance of Arndt-endobronchial blocker (Arndt) combined with laryngeal mask airway (LMA) compared with left-sided double-lumen endobronchial tube (L-DLT) in morbidly obese patients in one-lung ventilation (OLV). In a prospective, randomized double-blind controlled clinical trial, 80 morbidly obese patients (ASA I-III, aged 20–70) undergoing general anesthesia for elective thoracic surgeries were randomly allocated into groups Arndt (n=40) and L-DLT (n=40). In group Arndt, a LMA™ Proseal was placed followed by an Arndt-endobronchial blocker. In group L-DLT, patients were intubated with a left-sided double-lumen endotracheal tube. Primary endpoints were the airway establishment, ease of insertion, oxygenation, lung collapse and surgical field exposure. Results showed similar ease of airway establishment and tube/device insertion between the two groups. Oxygen arterial pressure (PaO2) of patients in the Arndt group was significantly higher than L-DLT (154±46 vs 105±52 mmHg; P<0.05). Quality of lung collapse and surgical field exposure in the Arndt group was significantly better than L-DLT (effective rate 100 vs 90%; P<0.05). Duration of surgery and anesthesia were significantly shorter in the Arndt group (2.4±1.7 vs 3.1±1.8 and 2.8±1.9 vs 3.8±1.8 h, respectively; P<0.05). Incidence of hoarseness of voice and incidence and severity of throat pain at the post-anesthesia care unit and 12, 24, 48, and 72 h after surgery were significantly lower in the Arndt group (P<0.05). Findings suggested that Arndt-endobronchial blocker combined with LMA can serve as a promising alternative for morbidly obese patients in OLV in thoracic surgery.